(2x-3)*(x+4)=6

Simple and best practice solution for (2x-3)*(x+4)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)*(x+4)=6 equation:



(2x-3)(x+4)=6
We move all terms to the left:
(2x-3)(x+4)-(6)=0
We multiply parentheses ..
(+2x^2+8x-3x-12)-6=0
We get rid of parentheses
2x^2+8x-3x-12-6=0
We add all the numbers together, and all the variables
2x^2+5x-18=0
a = 2; b = 5; c = -18;
Δ = b2-4ac
Δ = 52-4·2·(-18)
Δ = 169
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{169}=13$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-13}{2*2}=\frac{-18}{4} =-4+1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+13}{2*2}=\frac{8}{4} =2 $

See similar equations:

| -7m+7=9+4m | | 0.5t=0.4+.03t | | (x+3)*3+2=4+2 | | (4/3p)=(3/2p)+4/3 | | 14=2y+6 | | n+18+3n-16=6n-20 | | 3x2=11x-31 | | 7x-4=-2x+1+9x-5 | | (x+1)​2​​−36=0 | | 8x+4=-4x+12 | | 5(x-2)=-3x+41 | | x+5/6=41/36 | | 21=-3t | | 5x10(x+3)+25(x+5)=435 | | 8x4=-4x+12 | | 3+(3+2)4+100=z | | 27x2+7x+27=0 | | 2(4x+1)=-2(2x-3)-3x | | 5(3x+2x)-3=52 | | 2+4g=16-3g | | 2(x+4)-5=2x+3 | | (t-8)(t+3)=t-8 | | 12-(1/5r)=2r+1 | | 100x^2=1 | | 4x-2=3x+4 | | 14=31.7–3x | | (1/4x)-4=(3/8x) | | -37=11x-4 | | -20+-4x=-6x | | 3y2-33y=-84 | | X+128=68+x | | 2(4x+1)=-2(2x-3x)-3x |

Equations solver categories